PI3K/mTOR/S6K signaling pathway – new players and new functional links - Filonenko, V.V. (Вiopolymers and Cell, 2013)
This review summarizes experimental data related to the studies of PI3K/mTOR/S6K signaling conducted at the department of cell signaling. Analysis of novel S6Ks protein-protein interactions provided valuable information for understanding molecular mechanisms of regulation of S6Ks functional activity and subcellular localization mediated by PKC, CK2 and ROC1 ubiquitin ligase. We discuss the identification and functional analysis of novel isoform of ribosomal protein S6 kinase – S6K2 and of mTOR kinase – mTOR, as well as their oncogenic properties. Identification of CoA synthase responsible for last two steps in CoA biosynthesis and characterization of its interactions with S6K1 and other signaling molecules uncovere a potential link between mTOR/S6K signaling pathway and energy metabolism through regulation of CoA biosynthesis. The data concerning new molecular mechanisms of CoA synthase regulation are presented. В огляді представлено експериментальні результати дослідження сигнального шляху PI3K/mTOR/S6K, отримані у відділі сигнальних систем клітини. Аналіз нещодавно виявлених білково-білкових взаємодій S6K надає важливу інформацію для розуміння молекулярних механізмів регуляції функціональної активності S6K та її субклітинної локалізації за участі PKC, CK2 і убіквитинлігази ROC1. Обговорюються дані щодо ідентифікації і функціонального аналізу нової ізоформи кінази рибосомного білка S6 – S6К2 і mTOR- кінази – mTOR, а також їхніх онкогенних властивостей. Ідентифікація CoA-синтази, що є відповідальною за два останніх етапи біосинтезу CoA, а також характеристика її взаємодії з S6K1 та іншими сигнальними молекулами свідчать про існування потенційного зв’язку між сигнальним шляхом mTOR/S6K та енергетичним метаболізмом, опосередкованого регуляцією біосинтезу CoA. Наведено дані стосовно виявлених молекулярних механізмів регуляції активності синтази СоА. В обзоре представлены экспериментальные результаты исследования сигнального пути PI3K/mTOR/S6K, полученные в отделе сигнальных систем клетки. Анализ вновь выявленных белково-белкових взаимодействий S6K дает ценную информацию для понимания молекулярных механизмов регуляции функциональной активности S6K и ее субклеточной локализации при участии PKC, CK2 и убиквитинлигазы ROC1. Обсуждаются данные, касающиеся идентификации и функционального анализа новой изоформы киназы рибосомного белка S6 – S6К2 и mTOR киназы – mTOR, а также их онкогенных свойств. Идентификация CoA-синтазы – фермента, отвечающего за два последних этапа биосинтеза СоА, и анализ ее взаимодействия с S6K1 и другими сигнальными молекулами свидетельствуют о существовании потенциальной связи между сигнальным путем mTOR/S6K и энергетическим метаболизмом, опосредованным регуляцией биосинтеза СоА. Приведены данные о выявленных молекулярных механизмах регуляции синтазы СоА.